Photoemission and energy gap of MgWO 4 particles connecting as nanofibers synthesized by electrospinning-calcination combinations - Wannapop S. (2014)
Mixtures of magnesium acetate tetrahydrate ((CH 3COO) 2Mg·4H 2O), ammonium tungstate tetrahydrate ((NH 4) 6W 7O 24·4H 2O), and poly(vinyl alcohol) with the molecular weight of 72,000 were electrospun through a +15 kV direct voltage to form fibers on ground flat aluminum foils. The electrospun fibers of 1.5, 3.0, and 4.5 mmol of each starting material containing 1.3 g poly(vinyl alcohol) were further calcined at 500-700 °C for 3 h constant length of time. At 500 and 600 °C calcination, both monoclinic and anorthic phases of MgWO 4 particles with different sizes connecting as fibrous assemblies were detected. Upon increasing the calcination temperature to 700 °C, only monoclinic phase of facet nanoparticles interconnecting along the fibrous axes with 4.19 eV indirect band gap and 461 nm photoemission was synthesized. In the present research, formation of MgWO 4 molecules as well as nucleation and growth of nanoparticles was also proposed. © 2012 Elsevier B.V. All rights reserved.